OHP-003 Applying different scales for calculating the patient's anticholinergic load – five case examples. (14th February 2016) - Mayer, T; Haefeli, WE; Seidling, HM
Abstract : Background: The risk of physical and cognitive adverse events caused by the patient's anticholinergic drugs is referred to as anticholinergic load. Currently, the anticholinergic load can be calculated according to 12 diverse scales, which use different principles for defining the anticholinergic properties of drugs. In addition, one equation (Drug Burden Index) is available which considers the actual prescribed dose. Purpose: Due to varying identification and scoring criteria for anticholinergic drugs, the patient's load calculated as the sum of the drugs' scores differs with the scale used, thus questioning their usefulness. To illustrate the extent of variation, we applied the scales to five medication profiles typical of elderly patients. Material and methods: We set up five exemplary medication profiles each containing between 2 and 4 anticholinergic drugs: regularly prescribed drugs (doxepine, amitriptyline), as needed medication (cetirizine) and specific dosage forms (fentanyl patch). The drugs' anticholinergic properties were classified into scoring categories according to the scales and the resulting total load was calculated for each medication. Results: The 12 scales included 17–154 drugs with scores ranging from 0.7 to 1470 (most scales: score 1–3). On average, the medications' total load was calculated with 6 (of 12) scales as the drugs were not considered in all scales. Amitriptyline in medication one was the only drug rated similarly by 8 of 12 scales (score of 3). In medication two, the score for doxepine (0–50) and the total load (0–100) varied extensively. Medication profile three included as needed medication (score 0–2 for cetirizine) and medication four contained a specific dosage form (score 0–1 for fentanyl patch) both revealing a total load between 0 and 4. The anticholinergic drug tiotropium (medication five) is not considered in any scale and hence the total load varied only from 0 to 2. Conclusion: The scales used revealed extensive differences in identifying and scoring anticholinergic drugs and yielded diverse load values in the set up medication profiles. Hence the anticholinergic load strongly depends on the scale used, and further research must clarify which concept of calculation best predicts anticholinergic load. Conflict of interest.